Histopathological characterisation of retinal lesions associated to Diplostomum species (Platyhelminthes : Trematoda) infection in polymorphic Arctic charr Salvelinus alpinus - Padrós, Francesc; Knudsen, R.; Blasco-Costa, I. (International Journal for Parasitology: Parasites and Wildlife, 2018)
Altres ajuts: SNSF/31003A_169211/1 The eye represents an immune privileged organ where parasites can escape host reactions. This study provides the first systematic evidence of the pathology associated with Diplostomum sp. infection in the eye retina of fish (i.e. Arctic charr). Histological sections showed that the trematodes caused mechanical disengagement between the retinal pigmentary epithelium and the neurosensory retina, with damaged cones and rods in the outer segment and epithelium reduced to a single layer of pigmentary cells. The metacercariae were "floating" in possibly fluid-filled vesicles together with several round cells, mostly located in the anterio-dorsal and anterio-ventral areas of the eye near the iris. The round cells may indicate internal retinal damage repair mechanisms, without connections to the general immune system. Metacercariae intestines contained pigmented cellular debris indicating that they feed on retinal epithelium. These retinal lesions may have similar vision effects as focal retinal detachment in vertebrates. Diplostomum metacercaria alters fish visual acuity but may in a lesser degree lead to a severe or total visual impairment because of repairing mechanisms. The pathology in the retina seems thereby to be dependent on fish size, age and dose.